The Four Elements in Low-Vision Rehabilitation Service - Subramaniam, Suresh (West Kazakhstan Medical Journal, 2023)
This article addresses the critical issue of low-vision rehabilitation (LVR) services, focusing on the challenges faced by visually impaired patients, particularly those with central visual field limitations and visual acuity of 3/60 or worse in the better eye. Glaucoma, a chronic progressive optic neuropathy, poses a significant threat to vision and quality of life. Despite the absence of a definitive cure, various treatment modalities aim to control and slow down its progression. However, the impact of glaucoma-related structural and functional vision loss on patients’ quality of life is profound. Visual rehabilitation plays a pivotal role in guiding patient-centered therapeutic decisions, yet it remains underutilized for glaucoma patients. Understanding the available LVR is crucial in developing new tools and approaches. This article provides an overview of LVR options for visually impaired individuals and emphasizes the importance of comprehensively assessing and addressing their needs, both in terms of visual function and overall well-being.